Selective Janus Kinase Inhibition Preserves Interferon-Λ-mediated Antiviral Responses - Schnepf, Daniel (Sci Immunol, 2021)
Inflammatory diseases are frequently treated with Janus kinase (JAK) inhibitors to diminish cytokine signaling. These treatments can lead to inadvertent immune suppression and may increase the risk of viral infection. Tyrosine kinase 2 (TYK2) is a JAK family member required for efficient type I interferon (IFN-α/β) signaling. We report here that selective TYK2 inhibition preferentially blocked potentially detrimental type I IFN signaling whereas IFN-λ-mediated responses were largely preserved. In contrast, the clinically used JAK1/2 inhibitor baricitinib was equally potent in blocking IFN-α/β or IFN-λ-driven responses. Mechanistically, we showed that epithelial cells did not require TYK2 for IFN-λ-mediated signaling or antiviral protection. TYK2 deficiency diminished IFN-α-induced protection against lethal influenza virus infection in mice but did not impair IFN-λ-mediated antiviral protection. Our findings suggest that selective TYK2 inhibitors used in place of broadly acting JAK1/2 inhibitors may represent a superior treatment option for type I interferonopathies to counteract inflammatory responses while preserving antiviral protection mediated by IFN-λ.